Strategi Generasi Milenial dalam Mengelola Risiko Usaha Kecil Toko Madura: Pendekatan Kualitatif Berbasis Nilai Islam dan Digitalisasi Bisnis - Aria, M. Yusuf; Syafira, Suci Reza; Hana, Ubaid Aisyul; Rachmadian, Muhammad Nadhim (AL-UJRAH, 2025)
Abstract This study aims to analyze the strategies of millennials in managing the risks of small businesses in Madura Shops using a qualitative approach based on Islamic values and business digitalization in the North Gresik region. In the context of increasingly dynamic market competition, millennials play an important role as agents of economic transformation who are adaptive to technology and oriented towards business sustainability. A qualitative approach was used through in-depth interviews and observations of small businesses managed by millennials. SWOT analysis was applied to identify the strengths, weaknesses, opportunities, and threats faced in business risk management. The results of the study show that Islamic values, such as honesty (shiddiq), trustworthiness, and social responsibility (falah), form the basis for ethical and fair business decision-making. Meanwhile, business digitalization through the use of social media, e-commerce, and digital payment systems can increase efficiency and expand market reach. With an IFAS value of 2.44 and an EFAS value of 2.85, the business is positioned in the aggressive (growth-oriented) strategy quadrant, which means that business actors need to maximize external opportunities through internal strengths based on innovation and sharia principles. This study emphasizes the importance of integrating Islamic spirituality and digital technology in building the resilience of small businesses in the modern economy. Keywords: Risk Strategy, Millenial Generation, Islamic Values, Business Digitalization